How are molecular crowding and the spatial organization of a biopolymer interrelated - Jeon, Chanil; Hyeon, Changbong; Jung, Youngkyun; Ha, Bae-Yeun (Royal Society of Chemistry, 2016)
In a crowded cellular interior, dissolved biomolecules or crowders exert excluded volume effects on other biomolecules, which in turn control various processes including protein aggregation and chromosome organization. As a result of these effects, a long chain molecule can be phase-separated into a condensed state, redistributing the surrounding crowders. Using computer simulations and a theoretical approach, we study the interrelationship between molecular crowding and chain organization. In a parameter space of biological relevance, the distributions of monomers and crowders follow a simple relationship: the sum of their volume fractions rescaled by their size remains constant. Beyond a physical picture of molecular crowding it offers, this finding explains a few key features of what has been known about chromosome organization in an E. coli cell.
Keywords: Escherichia-Coli Chromosome; Rna-Polymerase; Physiological Consequences; Bacterial Chromosomes; Dynamics Simulation; Ring Polymer; Confinement; Dna; Transcription; Interact